The evolution of eastern Sichuan basin, Yangtze block since Cretaceous: constraints from low temperature thermochronology - Shi, Hongcai; Glasmacher, Ulrich A. (Journal of Asian earth sciences, 2016)
In Yangtze block (South China), there is a well-developed Mesozoic thrust system extended through the Xuefeng and Wuling mountains in the southeast to the Sichuan basin in the northwest. We present 11 apatite fission-track (AFT) data and 11 (U-Th-Sm)/He ages to unravel the low temperature thermal history of a part of the system located in the eastern Sichuan basin. The fission-track data are interpreted using a grain-age deconvolution algorithm with inverse thermal modeling of track length, grain ages and mineral composition proxy data. Results suggest that apatite fission-track ages range between 99.3±8.1 and 51.0±4.0Ma, and the apatite (U-Th-Sm)/He ages between 58.3±3.5Ma and 14.2±0.9. The spatial distribution of these ages shows a trend decreased from SE to NW gradually, which supports the idea of a prolonged, steady-state rock uplift and erosion process across the eastern Sichuan basin. Thermal history modeling of the combined FT and (U-Th-Sm)/He datasets reveal a common three stage cooling history: (1) initial stage of rapid cooling that younger to the east during pre-Cretaceous, (2) following by a period of relative (but not perfect) thermal stability at ∼65-50°C, (3) and then a new rapid cooling stage that initiated in all samples between ∼15 and 20Ma. The first rapid cooling at a rate of ⩾1.5°C/Ma is associated with coeval tectonism in nearby regions, which result in folds and faults of the eastern Sichuan basin. Early-mid Cenozoic thermal stability is contributed to the extension widely occurring in the eastern China continent at which the average cooling rate decreased to ∼0.16°C/Ma. Causes for speculative accelerated cooling after ca. 20-15Ma with a rate of ⩾1.2°C/Ma may be a far-field effect of upward and eastward growth of the Tibetan Plateau but could also be related to climate effects. In a whole, this paper analyzes the several Mesozoic and Cenozoic tectonic events influence to the patters of regional denudation.